Gender and Sexuality in Contraceptive Advertising in Bangladesh (1972-2011) – An Audience Perspective (Journal of the Asiatic Society of Bangladesh, Humanities, 2023)
‘In our time sex outside marriage was a taboo. But now it is increasingly happening [...]. In today’s context [...] it is very important to build awareness.’ Such perspective from Mitiis indicative of a contemporary phenomenon with regard to portraying pre/extra marital sexual intimacy in condom advertisements (ads) in Bangladesh. Drawing from research findings of 36 in-depth interviews, this paper interrogates women’s responses to new-old (non)normative presence of sexuality in these ads, across three social classes and three generations. The paper reflects how social class, age and other identities might shape mediated conversations about normativity vs. shifting “realities” of sexuality in contemporary Bangladesh. The discussions suggest although some women want to see a reflection of the “real”, which is, the increasing practices of pre/extra marital sex, many like to see the “ideal”, the “traditional” forms of sexuality depictions in these ads. What seems significant – with regard to the portrayal of sexual intimacy, a majority of the women talk at a much-generalised level: not always tying into their experiences or their own families. They continuously engage with a dialogue with the ads, and often compare an idealised earlier period with “now” which they consider problematic.Journal of the Asiatic Society of Bangladesh (Hum.), Vol. 68(2), 2023, pp. 175-192